Pengaruh Literasi Sosial terhadap Pola Interaksi Sosial Siswa Pengguna Gawai di SMK Emmanuel Medan - Sunyianto, Sunyianto; Yusrin Karauna; Antonius Wilson Sembiring; Kerisman Halawa; Waspada Zebua (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
The study aims to assess the influence of social literacy on social interaction patterns of students at SMK Emmanuel Medan who use gadgets. This study uses quantitative and descriptive methods. Purposive sampling technique was used to select the sample for the study. Data were collected through questionnaires distributed to 42 students in class XI of SMK Emmanuel Medan. The data were analyzed using multiple linear regression. The results show that social literacy benefits students' device use at SMK Emmanuel Medan. Therefore, it can be concluded that social literacy benefits students' device use in school.